The COVID-19 Pandemic and African Aviation : Policy Note - World Bank (Washington, DC: World Bank, 2022)
The COVID-19 pandemic is posing an existential threat to the air transport sector globally, including in Africa. Due to sustained and significant loss of revenue coupled with the presence of several fixed and quasi-fixed inputs in this sector, the survival of carriers is questionable in the short term. This could lead to bankruptcies of important African-based airlines resulting in severe loss of connectivity, especially in the intra-African markets. If history is any guide, within the current regulatory environment that restricts market access and the ownership and control of airlines, it could be a long time before another airline fills the void left by a defunct airline in Africa. This challenge is further compounded by the difficulty of accessing capital and the high cost of (re)training and attracting the highly skilled labor typically needed to run a viable airline. The objective of this policy note is to explore policy and operational strategies to build back a safe and competitive air transport sector in the aftermath of the COVID-19 crisis in Africa. It focuses on four broad areas: it provides a short status update on the impact of the pandemic; reviews pre-COVID-19 sector challenges from the supply, demand, and regulatory sides; tracks and analyzes government financial support and bailouts to airlines in the aftermath of the crisis globally; and identifies and recommends operational and policy responses to mitigate the impact of the crisis and put the aviation sector on a sustainable development path.